Ne dadim vzorvat' zemlyu! - Kapitan, A. A (1984)
Series of multi-coloured hands pushing away a nuclear warhead labelled US Original title; Не дадим взорвать землю! Suggested translation: We will not let them blow up the earth! PO-0079